PEComa: A Perivascular Epithelioid Cell Tumor in the Liver—A Case Report and Review of the Literature - Faseeh Khaja; Allison Carilli; Said Baidas; Aravindhan Sriharan; Shanedelle Norford (Case Reports in Medicine)
Perivascular epithelioid cell tumors are soft tissue tumors that can occur in various locations in the body whose incidence is rising. Hepatic PEComas are quite rare and diagnosis involves positivity of Melan-A and HMB45 on immunohistochemistry. Usual treatment is surgery for benign tumors and chemotherapy including mTOR inhibitors for malignant tumors. Here we discuss the radiological and pathological diagnosis, evaluation, and management of a hepatic PEComa. We describe a 51-year-old patient who was diagnosed incidentally after unusual physical exam findings.